Peran Kepala Sekolah Sebagai Supervisor Untuk Meningkatkan Kualitas Pembelajaran di SD Negeri - Susti, Wira; Somantri, Manap; Connie, Connie (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2025)
This study aimed to analyze the role of principals as supervisors in improving the quality of learning at SD Negeri 83 Bengkulu Selatan. The research focused on the planning, implementation, and evaluation of academic supervision, including its supporting and inhibiting factors. A qualitative approach was employed, with data collected through semi-structured interviews, participatory observation, and documentation analysis. The data were analyzed using Miles and Huberman’s interactive model, which consisted of data reduction, data display, and conclusion drawing. The findings showed that the principal conducted supervision in a participatory manner by involving teachers in program planning, carrying out reflective dialogue-based supervision, and providing constructive follow-up. Supporting factors included participatory leadership, teacher commitment, and school committee support, while the main obstacles were limited time, inadequate learning facilities, and teacher resistance. The study concluded that humanistic and collaborative supervision played a vital role in improving teacher professionalism and learning effectiveness. Furthermore, it suggested that future supervision practices could be developed through Professional Learning Communities and the use of simple digital technology to strengthen sustainability and effectiveness.